FINANCIAL RISK MANAGEMENT AND FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN UGANDA: A CASE STUDY OF CENTENARY BANK, MUKONO BRANCH - Lenia Doreen (My University, 2024)
A case study of Centenary Bank's Mukono branch was used in the study to examine the connection between financial risk management and the financial performance of commercial banks in Uganda. With regard to Centenary Bank, Mukono, it specifically examined the relationship between financial risk identification and financial performance, established the relationship between financial risk assessment and financial performance, and evaluated the relationship between financial monitoring and financial performance. A cross-sectional survey research design was employed to conduct the study, and both quantitative and qualitative research methods were applied. Purposive and basic random sample techniques were employed together with questionnaires and interviews to gather the data. Despite just 44 responders, the survey also included a sample size of 48 management and staff members from the Centenary Bank branch in Mukono. The results showed that the bank's strong operational risk mitigation methods, clear processes and systems for recognizing possible financial concerns, and encouragement of employee reporting all greatly enhance financial performance. Furthermore, the bank's financial performance is positively impacted by its efficient use of cutting-edge risk assessment tools and models as well as its dedication to routinely reviewing and updating these procedures. Furthermore, there is a significant association between improved financial performance and the bank's use of cutting-edge technology to track market trends, conduct routine internal audits, and thoroughly evaluate financial statements. These results highlight the significance of proactive risk management techniques and financial oversight procedures for the long-term viability of Centenary Bank. According to the study, Centenary Bank should prioritize compliance and internal audits, foster a culture of continuous improvement, strengthen its risk identification and assessment processes through knowledgeable evaluations and regular updates, improve employee engagement in risk reporting, optimize risk mitigation strategies, and emphasize long-term financial sustainability by striking a balance between prudent management and risk-taking for stability and resilience in shifting economic conditions.